Treatment of Infertility through the Qur'an: Shifting the Function of al-Syifa' from Spiritual Disease Treatment to Physical Medicine - Ichwan, Mohammad Nor; Rohmah, Nihayatur (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2023)
Al-Qur’an, besides proclaiming itself as a guide for the man (huda li al-nas), also serves as a cure or healer (shifa') against all kinds of diseases, especially spiritual conditions. In the Community of Therapy Sky Line Two With Prayer, the Qur'an serves as a medium of infertility treatment. Infertility occurs when a husband and wife do not have children, even though they are sexually active. Besides being caused by medical factors, infertility is also caused by non-medical factors, such as genie or magic disorders. This article aims to elaborate and, at the same time, prove the success of infertility treatment through the medium of Qur'anic verses carried out by Therapy Sky Line Two With Prayer. Methodologically, this article uses field research whose primary sources are obtained through observation, structured interviews, and documentation. The collected data was then analyzed using a phenomenological approach. The findings of this article show that the Qur'an can not only cure spiritual diseases but can also be used as a medium to treat infertility. This article also found that the verses of the Qur'an recited to people with infertility can make their hearts calm, more pleased with His decrees, and also more grateful for the blessings He has given. This attitude is a fundamental thing that is needed for those who have not been blessed with offspring. Hence, they feel confident that chanting the verses of the Qur'an can stimulate people with infertility and make them pregnant and have the desired offspring.